Aux racines de l'industrialisation éducative, la distance - Pierre Mœglin (Centre National d'Enseignement à Distance, 2020)
This article shows how, using the prism of distance, Jacques Perriault exposes a genealogy of the industrialization of education. Gathered and put together, his analyses suggest that this industrialization results from a triple turn: the communicational one, which converts the technicization of teaching into the mechanization of educational communication; the cognitive turn, which attributes to the reflexive potential of communication machines the rationalizing power of a medium; and finally, the ideological turn, which disqualifies traditional educational craft practices to promote the industrial values and ideals of modernity and educational productivism.